Fantastic, surreal and monstrous in Zdzislaw Beksinski - Hipólito, Rodrigo (Farol, 2023)
This text works with the interpretative possibilities, development in the poetic process and motivations for the wide circulation of the works of the Polish artist Zdzislaw Beksinski in the post-internet scenario. Specifically, we deal with works from his so-called “fantastic period”. Through a detailed description of some of his paintings and comparison with analyzes already carried out on his works, we point out characteristics of his figuration present in his sketches and drawings, the use of elements from the Cold War imaginary and possible references within the Polish and surrealism.